Osteopontin is linked with AKT, FoxO1, and myostatin in skeletal muscle cells. Issue 6 (13th August 2017) - Nghiem, Peter P.; Kornegay, Joe N.; Uaesoontrachoon, Kitipong; Bello, Luca; Yin, Ying; Kesari, Akanchha; Mittal, Priya; Schatzberg, Scott J.; Many, Gina M.; Lee, Norman H.; Hoffman, Eric P.
ABSTRACT: Introduction : Osteopontin (OPN) polymorphisms are associated with muscle size and modify disease progression in Duchenne muscular dystrophy (DMD). We hypothesized that OPN may share a molecular network with myostatin (MSTN). Methods : Studies were conducted in the golden retriever (GRMD) and mdx mouse models of DMD. Follow‐up in‐vitro studies were employed in myogenic cells and the mdx mouse treated with recombinant mouse (rm) or human (Hu) OPN protein. Results: OPN was increased and MSTN was decreased and levels correlated inversely in GRMD hypertrophied muscle. RM‐OPN treatment led to induced AKT1 and FoxO1 phosphorylation, microRNA‐486 modulation, and decreased MSTN. An AKT1 inhibitor blocked these effects, whereas an RGD‐mutant OPN protein and an RGDS blocking peptide showed similar effects to the AKT inhibitor. RMOPN induced myotube hypertrophy and minimal Feret diameter in mdx muscle. Discussion : OPN may interact with AKT1/MSTN/FoxO1 to modify normal and dystrophic muscle. Muscle Nerve 56 : 1119–1127, 2017